Revealing the Sanctity of the Eternal Cosmic Hierarchy: A Comparative Analysis of Javanese Mysticism and Islamic Sufism - Riyanto, Waryani Fajar (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2023)
Most religious cosmology studies focus on the microcosm and macrocosm; however, the origin of cosmic mysticism is the eternal cosmos extensively studied in cultures and religions such as Javanese and Islam. This study aimed to examine the different interpretations of the sanctity of the eternal cosmos hierarchy in Javanese mysticism and Islamic Sufism. The eternal cosmos is referred to as jagad langgeng and ‘ālam akbar in Javanese mysticism and Islamic Sufism, respectively. This qualitative study conducted document reviews to obtain primary and secondary data analyzed through comparative analysis. This study aimed to examine the concept of the five eternal cosmos hierarchies of the absolute universe, lordness universe, transcendent universe, celestial universe, and terrestrial universe. The findings reinforce the concept of cosmic spirituality, divine cosmology, and wisdom of cosmology as well as theoretical and practical implications. Theoretically, the study contributes to the integration of sacred Javanese Islamic, and Western cosmologies and the clarification of the eternal and temporary cosmos in theological discussions. The findings also have practical implications in creating eco-leadership based on hasta brata values.